Comparative study on bone mineral density in premenopausal patients with estrogen receptor-positive breast cancer in ASTRRA Study: a 5-year follow-up study - Shin, Eunju; Kim, Seung Il; Park, Min-ho; Kim, Hyun-Ah; Jung, Yongsik; Ryu, Jai Min; Park, Eun Hwa; Kim, Sung Yong; Lee, Eun-Gyeong; Lee, Min Hyuk; Park, Jung Ho; Im, Seock-Ah; et al. (Frontiers in Oncology, 2025)
PurposeWe compared the impact of tamoxifen alone or with ovarian function suppression (OFS) on bone mineral density (BMD) in premenopausal patients after chemotherapy.MethodsOf 1483 premenopausal women enrolled in the ASTRRA study, we included 522 who underwent BMD examinations at diagnosis and 3 and 5 years after diagnosis. All BMD measurements were performed using the same scanner in each center across different time points. Patients were stratified into three groups: within the expected range for age (A, Z-score>-1.0), below the expected range (B,-2.0≤ Z-score ≤-1.0), and low bone mineral density for chronological age (C, Z-score< -2.0) groups. We examined changes in groups from baseline to >3-year and 5-year periods to identify any deterioration in BMD. We conducted a subset analysis using the Asan Medical Center (AMC; n=141) data, focusing on the absolute value of bone density (in g/cm2 unit).ResultsThe 522 included patients (median age, 41.1 years) had a higher bone loss incidence in the OFS addition group at baseline (p=0.028). The tamoxifen-only and tamoxifen+OFS groups did not differ significantly in terms of changes in BMD categories from baseline to 3 (p=0.567) or 5 years (p=0.600). The OFS addition group had a significantly increased risk of BMD deterioration when randomized at the first visit (odds ratio=2.970, p=0.008). Within the AMC subset, the OFS addition group exhibited significantly decreased BMD in the spine (p=0.023) and femur (p=0.040) from the baseline to 3-year period. A non-significantly decreased BMD occurred from the baseline to 5 years in the spine and femur.ConclusionOur findings highlighted the deleterious impact on BMD following OFS addition, compared with tamoxifen only treatment. Early OFS exerted an even more detrimental influence on bone health in premenopausal patients with estrogen receptor-positive breast cancer and recovered ovarian function.AbbreviationsANOVA, analysis of variance; BMD, one mineral density; CTIBL, Cancer treatment-induced bone loss; DXA, dual-energy X-ray absorptiometry; HER2 human epidermal growth factor receptor 2; L-spin, lumbar spine; OFS, ovarian function suppression; TAM, tamoxifen.